Key concepts in popular music - Shuker, Roy, 1948- (London : Routledge, 1998)
Key Concepts in Popular Music presents a comprehensive A-Z glossary of the main terms and concepts used in the study of popular music. The book includes definitions of key musical genres, from bhangra to punk rock; musical subcultures, from hippies to goths; methodologies, from Marxism to postmodernism; musicological terms, from harmony to sampling; musical phenomena, from girl groups to concept albums. Each entry includes suggestions for further reading and is cross-referenced with related concepts.
Includes bibliographical references (p. 318-345) and indexes.
Keywords: Popular music -- Encyclopedias